2003
DOI: 10.1096/fj.02-0621fje
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 inhibits cell death in yeast and mammalian cells and is abundantly expressed in human breast carcinoma

Abstract: Apoptosis is a fundamental biological process used to eliminate unwanted cells in a multicellular organism. An increasing number of regulatory proteins have been identified that either promote or inhibit apoptosis. For tumors to arise, apoptosis must be blocked in the transformed cells, for example by mutational overexpression of anti-apoptotic proteins, which represent attractive target proteins for molecular therapy strategies. In a functional yeast survival screen designed to select new anti-apoptotic mamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
130
0
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 179 publications
(138 citation statements)
references
References 65 publications
4
130
0
3
Order By: Relevance
“…We performed a functional yeast survival screen with a human breast carcinoma-derived cDNA library in order to identify novel anti-apoptotic proteins involved in tumorigenesis. 17,18 Among others, we isolated a cDNA clone coding for an N-terminal deletion mutant of the anti-apoptotic Aven protein. This clone, which efficiently suppressed yeast cell death induced by the proapoptotic C. elegans protein CED-4 (see Supplementary Figure 1), lacks the coding sequence for the N-terminal 179 aa (amino acid) of the protein (DN-Aven 180-362).…”
Section: Resultsmentioning
confidence: 99%
“…We performed a functional yeast survival screen with a human breast carcinoma-derived cDNA library in order to identify novel anti-apoptotic proteins involved in tumorigenesis. 17,18 Among others, we isolated a cDNA clone coding for an N-terminal deletion mutant of the anti-apoptotic Aven protein. This clone, which efficiently suppressed yeast cell death induced by the proapoptotic C. elegans protein CED-4 (see Supplementary Figure 1), lacks the coding sequence for the N-terminal 179 aa (amino acid) of the protein (DN-Aven 180-362).…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10] Recently, accumulating data suggested that HMGB1 expression was correlated with tumor development. [10][11][12][13] Upregulated expression of HMGB1 has been found in many tumor types including lung cancer. 3 However, high-mobility group box 1 (hMGB1) has been implicated in a variety of biologically important processes, including transcription, DNa repair, differentiation, development and extracellular signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Bax-expression in plants causes localized tissue collapse in a manner resembling the hypersensitive response, a PCD response of plants in defense against pathogens [5]. Moreover, human or plant genes isolated from yeast genetic screens for Bax or Bak suppression have been associated with pro-survival effects when expressed in their native or a heterologous context [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%